ANALISIS KEBUTUHAN BACKPACKER TERHADAP MOBILE APPLICATION EFEKTIF DAN EFISIEN - Keni Dion; Intan Rizky Mutiaz (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
Labuan Bajo as a super priority, world class and super premium destination, has tourism differentiation compared to other tourist destinations, so that it attracts foreign tourists to visit. However, for backpacker tourists, seeking integrated information related to traveling to Labuan Bajo is one of the obstacles in the pre-trip process. Backpackers have to compare the cheapest prices from one application to another, so they experience difficulties in organizing trips manually. This resulted in the pre-trip process being inefficient and ineffective. Based on this description, this study aims to identify the need for backpacker travel guides to facilitate the pre-trip process effectively and efficiently. The research was conducted using a qualitative approach through distributing questionnaires, in-depth interviews, comparative studies, and literature studies. The results of filling out the questionnaire by the respondents were then analyzed using a quantitative approach. The results of the analysis state that Indonesia has many popular travel applications, but none yet accommodate backpacker problems, so a special backpacker travel application is needed to make the travel process efficient and effective.Keywords: mobile travel application, backpacker, Labuan Bajo, organise effective and efficient travel